Peningkatan Pemahaman Peran Perguruan Tinggi Terhadap Layanan dan Pendampingan Hukum Bagi Usaha Kecil Mikro - Kurnianingsih, Marisa; Kuswardani, Kuswardani; Prakoso, Andria Luhur; Iksan, Muchamad (Civiliza Publishing, 2024)
The Constitution of the Republic of Indonesia Year 1945 mandates the government to strive for a national education system that emphasizes faith, piety and humanity based on the one and only god. Higher education carries the mandate of the 1945 Constitution, which is one of educating the nation's life, this mandate must be implemented by the government as a policy maker. Higher education is part of the national education system that has a strategic role in educating the nation's life and advancing science and technology by paying attention to pancasila. The tridharma of higher education carries 3 pillars, namely research, community service and learning. Universities and academicians have an important role in driving social change and progress in society. As agents of change, they have the potential to influence policy, champion social issues, and encourage innovation in various fields, including the economy. In recent years, the statistics on the growth and development of micro small businesses have achieved significant changes. Lecturers and students and other academicians are expected to synergize with each other to spread benefits in the community, the latest thoughts and the latest innovations for the sake of realizing a resilient and sustainable Indonesian economy.